Problematika Regulasi Pengelolaan Dana Abadi Umat: Disharmonisasi Kelembagaan dan Legal Standing - Muhammad Aziz Zakiruddin (Media Syari'ah, 2021)
Law Number 8 of 2019 concerning the Implementation of Hajj and Umrah Worship, discusses the polemic and disharmony of Law Number 34 of 2014 concerning Hajj Financial Management. The elimination and transfer of the functions and duties of the Badan Pengelola Dana Abadi Umat (BP-DAU) to the Ministry of Religion resulted in disharmony. Not only in the regulatory aspect but in institutions. Some questions or problem formulations that arise in this paper are, what are the dynamics in the management of the Umat Endowment Fund? Second, what are the factors of institutional disharmony and legal aspects in the management of the Dana Abadi Umat? How is the impact of this disharmony on the management of the Dana Abadi Umat? In answering these questions the authors use the Library research method with a statutory approach (Statue approach), which is built on legal theories, tiered legal theory "The Hierarchy Of law", then the principles of legal preference, as well as Synchronization and Harmonization of laws. invite. This dualism is caused by disharmony between the PKH law and the PIHU law, disharmony in the PIHU Law is built on various factors and aspects, so that the PIHU Law is deemed not to apply the principle of legacy and the principle of forming good legislation. This dualism in the management of the DAU can affect the existence of BPKH and open up conflicts and problems in the future.Undang-Undang Nomor 8 Tahun 2019 tentang Penyelenggaran Ibadah Haji dan Umrah, menyisakan polemik dan disharmonsasi terhadap Undang-Undang Nomor 34 tahun 2014 tentang Pengelolaan Keuangan Haji. Penghapusan dan pengalihan fungsi dan tugas Badan Pengelola Dana Abadi Umat (BP-DAU) kepada Kementerian Agama, menyebabkan disharmonisasi. Tidak hanya dalam aspek regulasi namun dalam kelembagaan. Beberapa pertanyaan atau rumusan masalah yang muncul dalam tulisan ini yaitu, bagaimana dinamika yang terjadi dalam pengelolaan Dana Abadi Umat? Kedua, apa yang menjadi faktor disharmonisasi kelembagaan dan legal aspek dalam pengelolaan Dana Abadi Umat? Bagaimana dampak disharmonisasi tersebut pada pengelolaan Dana Abadi Umat? Dalam menjawab pertanyaan tersebut penulis menggunakan metode Library research dengan pendekatan perundang -undangan (Statue approach), yang dibangun atas teori-teori hukum, Teori hukum berjenjang “The Hierarchy Of law”, kemudian asas-asas preferensi hukum, serta Sinkronisai dan Harmonisai undang-undang. Dualisme ini disebabkan disharmonisasi diantara undang-undang PKH dan undang-undang PIHU, disharmonisai dalam UU PIHU dibangun atas berbagai faktor dan aspek, sehingga UU PIHU dinilai kurang menerapkan principle of legacy serta asas pembentukan perundangan yang baik. Dualisme dalam pengelolaan DAU ini dapat mempengaruhi eksistensi BPKH dan membuka konflik dan problem di masa yang mendatang.